Soil Acidification Aggravates the Occurrence of Bacterial Wilt in South China - Li, Shili; Liu, Yongqin; Wang, Jiao; Yang, Liang; Zhang, Shuting; Xu, Chen; Ding, Wei (Frontiers in Microbiology, 2017)
Soil acidification is a major problem in modern agricultural systems and is an important factor affecting the soil microbial community and soil health. However, little is known about the effect of soil acidification on soil-borne plant diseases. We performed a four-year investigation in South China to evaluate the correlation between soil acidification and the occurrence of bacterial wilt. The results showed that the average soil pH in fields infected by bacterial wilt disease was much lower than that in non-disease fields. Moreover, the proportion of infected soils with pH lower than 5.5 was much higher than that of non-infected soils, and this phenomenon became more obvious as the area of bacterial wilt disease increased at soil pH lower than 5.5 from 2011 to 2014. Then, in a field pot experiment, bacterial wilt disease developed more quickly and severely in acidic conditions of pH 4.5, 5.0 and 5.5. These results indicate that soil acidification can cause the outbreak of bacterial wilt disease. Further experiments showed that acidic conditions (pH 4.5-5.5) favored the growth of the pathogen Ralstonia solanacearum but suppressed the growth and antagonistic activity of antagonistic bacteria of Pseudomonas fluorescens and Bacillus cereus. Moreover, acidic conditions of pH 5.5 were conducive to the expression of the virulence genes PopA, PrhA, and SolR but restrained resistance gene expression in tobacco. Finally, application of wood ash and lime as soil pH amendments improved soil pH and reduced the occurrence of bacterial wilt. Together, these findings improve our understanding of the correlation between soil acidification and soil-borne plant diseases and also suggest that regulation of soil acidification is the precondition and foundation of controlling bacterial wilt.